2020
DOI: 10.1108/rpj-12-2019-0320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of post-heat treatment cooling on microstructure and mechanical properties of selective laser melting manufactured austenitic 316L stainless steel

Abstract: Purpose This paper aims to investigate the influence of different post-annealing cooling conditions, i.e. furnace cooling (heat treatment (HT) 1 – slow cooling) and air cooling (HT 2 – fast cooling), on the microstructure and mechanical properties of selective laser melting (SLM) built austenitic 316L stainless steel (SS). Design/methodology/approach Three sets of 316L SS samples were fabricated using a machine standard scanning strategy. Each set consists of three tensile samples and a cubic sample for micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 45 publications
(47 reference statements)
0
15
0
Order By: Relevance
“…Post-processing is also relevant in SLM. Waqar et al [ 15 ] found that microstructure and mechanical properties of SLMed SS316L components are influenced by different post-annealing conditions at which the cooling down takes place. Likewise, Gupta et al [ 16 ] found that higher angle layer rotation leads to a reduction in grain size, residual stress, and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Post-processing is also relevant in SLM. Waqar et al [ 15 ] found that microstructure and mechanical properties of SLMed SS316L components are influenced by different post-annealing conditions at which the cooling down takes place. Likewise, Gupta et al [ 16 ] found that higher angle layer rotation leads to a reduction in grain size, residual stress, and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the material behavior of the stent was considered isotropic and homogeneous assuming that the geometric effects (e.g. stent design, irregularities) outweigh the influence of material anisotropy with respect to the macroscopic mechanical behavior [27]. Although this approach is well established for L-PBF lattice structures [19,54,60,61], the direction-dependent properties of the stent should be further investigated (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…Compared to L-PBF 316L in the as-built condition, a reduction in the yield and tensile strength can be achieved with a simultaneous increase in ductility due the homogenization of the microstructure (e.g. increase in grain size and misorientation), the reduction of the δ-ferrite phase and the reduction of residual stresses by adequate heat treatment [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as-fabricated AM metallic materials, including 316L SS often produce novel microstructures that result in mechanical and functional properties that are on par with, or even better than, the wrought/cast counterparts [27][28][29][30][31][32][33]. Certain post-processing techniques are also applied to improve the surface finish and integrity, such as by aging, finish machining, and blasting [34,35], as well as altering the mechanical properties of AM parts as required by post-heat treatment and/or cooling [36]. Thus, HPT processing is a viable technique to further enhance the mechanical properties of AM 316L SS [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%